Neurogenesis in the Adult Hippocampus - Kempermann, Gerd (Cold Spring Harb Perspect Biol, 2015)
Of the neurogenic zones in the adult brain, adult hippocampal neurogenesis attracts the most attention, because it is involved in higher cognitive function, most notably memory processes, and certain affective behaviors. Adult hippocampal neurogenesis is also found in humans at a considerable level and appears to contribute significantly to hippocampal plasticity across the life span, because it is regulated by activity. Adult hippocampal neurogenesis generates new excitatory granule cells in the dentate gyrus, whose axons form the mossy fiber tract that links the dentate gyrus to CA3. It originates from a population of radial glia-like precursor cells (type 1 cells) that have astrocytic properties, express markers of neural stem cells and divide rarely. They give rise to intermediate progenitor cells with first glial (type 2a) and then neuronal (type 2b) phenotype. Through a migratory neuroblast-like stage (type 3), the newborn, lineage-committed cells exit the cell cycle and enter a maturation stage, during which they extend their dendrites into a the molecular layer and their axon to CA3. They go through a period of several weeks, during which they show increased synaptic plasticity, before finally becoming indistinguishable from the older granule cells.